Implementation of East Sumba Regent Regulation Number 33 of 2023 on Educational Services for Belief in God Almighty in Educational Units - Makatehu, Umbu Damu; Putra, Fadillah (Faculty of Law, Universitas Pekalongan, 2025)
Educational services for adherents of indigenous beliefs are a manifestation of the constitutional mandate to guarantee the rights of every citizen. This research aims to conduct an in-depth analysis of the implementation of the East Sumba Regent Regulation Number 33 of 2023 concerning Educational Services for Belief in God Almighty in Educational Units, with a case study on Marapu believers. Using a descriptive qualitative approach, data were collected through in-depth interviews with key stakeholders such as the Regent of East Sumba, the Head of the Education Office, foundation leaders, and educators, as well as through observation and documentation. Data analysis was carried out using the five-factor policy implementation framework from Khan and Khandeker (2016), which includes rational, management, organizational, bureaucratic, and political factors. The results show that in the rational factor, the policy objectives are clearly defined, but socialization to the grassroots community is still limited. In the management factor, a budget has been allocated, but implementation is constrained by the limited number and qualifications of educators and the inadequacy of Marapu-specific teaching modules. The organizational factor indicates strong leadership from the regional head and high motivation from various parties, but teamwork in the field needs to be optimized. The bureaucratic factor shows that an implementation structure is in place, but the competence and capacity of implementers at the school level still need improvement. Finally, in the political factor, there is strong political will and minimal inhibiting political pressure after initial dialogues, but harmony among all implementing actors must be continuously maintained. This study concludes that the policy implementation is proceeding with a strong legal and political foundation but faces significant challenges in managerial and technical aspects on the ground. ‎